Antenatal and postpartum comparison of HD-OCT findings of macula, retinal nerve fiber layer, ganglion cell density between severe preeclampsia patients and healthy pregnant woman - Abdullah Tok; Abdullah Beyoğlu (Hypertension in Pregnancy, 2020)
Aim To investigate the effects of severe preeclampsia on the retinal nerve fiber layer (RNFL), macula thickness and ganglion cell density in pregnancy and postpartum, using High Definition Optical Coherence Tomography (HD-OCT). Material and Method The study group included 28 stable pregnant patients diagnosed with severe preeclampsia and the control group, 28 age and gestational week-matched healthy pregnant women. HD-OCT measurements were taken by the same researcher using a Cirrus HD-OCT device and were repeated at 8 weeks postpartum. Results The mean systolic pressure, diastolic pressure, and intraocular perfusion pressure (IPP) values measured in pregnacy were determined to be higher in the preeclampsia group than in the control group (158.4 ± 7.3 vs.113.6 ± 6.8, 97.0 ± 5.7vs.73.8 ± 5.9 and 68.1 ± 3.9 vs.48.8 ± 3.3 mm Hg, respectively) (p < 0.05 for all). The mean RNFL, macula thickness, ganglion cell analysis, and intraocular pressure (IOP) values during pregnancy were determined to be similar in both groups (p > 0.05 for all). No significant difference was determined postpartum between the groups in respect of mean systolic pressure, diastolic pressure, RNFL, macula thickness, ganglion cell analysis, and IOP values (114.3 ± 5.0 vs 114.6 ± 5.9 mm Hg, 74.6 ± 5.1 vs.74.5 ± 5.5 mm Hg, 96.0 ± 7.3 vs. 95.9 ± 6.7 µm, 228.2 ± 18.9 vs.234.5 ± 15.4 µm, 81.8 ± 8.0 vs. 84.2 ± 4.6 µm, 14.1 ± 2.4 vs.13.8 ± 2, respectively) (p < 0.05 for all). Mean IPP during pregnancy was higher than the mean postpartum IPP in the severe pre-eclampsia group (68.1 ± 3.9 vs 49.1 ± 3.1 mm Hg) (p < 0.001). Conclusion This is the first study to have evaluated ganglion cell density of the retina, macula thickness, and RNFL using HD-OCT in severe pre-eclampsia cases, both during pregnancy and postpartum.